Rent-a-girlfriend. Volume 4 - Miyajima, Reiji (Kodansha Comics, 2020)
"You can rent a girlfriend, but can you buy love? Reeling from a bad breakup, Kazuya rents the beautiful, polite Chizuru for a date. But rock bottom might be so much lower than he thought! Chizuru is much more than the pretty face and sweet demeanor he thought he'd bargained for ... ENTER PLAYER 3. Even after an intense hot springs trip with his rental girlfriend, things are complicated for the still hap-less and deeply confused Kazuya."--Provided by publisher